2020
DOI: 10.1002/micr.30682
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the effects of venous super‐drainage in deep inferior epigastric artery perforator flaps for breast reconstruction

Abstract: Introduction: Venous congestion is the most common vascular complication of the deep inferior epigastric artery perforator (DIEP) flaps. Adding a second venous drainage by anastomosing a flap vein and a recipient vein (super-drainage) is considered the solution of choice. Evidence to support this procedure, had not yet been confirmed by an analysis of the literature. We aimed to provide this evidence. Materials and methods: We searched the literature (MedLine, Scopus, EMBASE, Cochrane Library, and Google Schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…44 45 In addition to relieving congestion, venous superdrainage using the SIEV has also been shown to significantly decrease both total and partial flap necrosis as well as takebacks for perfusion-related complications. 46 Prior studies have demonstrated that SIEVs with diameters ranging from 0.5 to 4.06 mm can be identified on US, 39 41 comparable to those reported using CTA. 47 Thus, US may be useful in identifying large caliber SIEVs suggestive of a dominant superficial venous drainage system and in preserving the SIEV for use in the event of unexpected venous congestion.…”
Section: Potential Applications Of Ultrasound In Diep Flap Planningmentioning
confidence: 66%
“…44 45 In addition to relieving congestion, venous superdrainage using the SIEV has also been shown to significantly decrease both total and partial flap necrosis as well as takebacks for perfusion-related complications. 46 Prior studies have demonstrated that SIEVs with diameters ranging from 0.5 to 4.06 mm can be identified on US, 39 41 comparable to those reported using CTA. 47 Thus, US may be useful in identifying large caliber SIEVs suggestive of a dominant superficial venous drainage system and in preserving the SIEV for use in the event of unexpected venous congestion.…”
Section: Potential Applications Of Ultrasound In Diep Flap Planningmentioning
confidence: 66%
“…In terms of partial flap necrosis general trends toward lower risks were identified, without being statistically significant ( 86 ). Another metaanalysis published in 2021 showed a statistically significant advantage of super-drainage to reduce venous congestion of the flap, partial flap necrosis, total flap necrosis and the need to take the patient back to surgery for perfusion-related complications ( 87 ). A systematic review of the literature published in 2015 reported an incidence of intraoperative venous congestion of the free abdominal flap during breast reconstruction of 2.8%.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the complication reporting of the studies included in the present studies makes the result unreliable. It also casts doubt on the validity of the previous reviews where meta-analyses seem to have been performed on unacceptably heterogenic data [ 72 , 73 ]. To advance the field of abdominally based free flaps and refine our techniques in a scientific manner, as well as enabling comparison of the result from different studies, further studies on standardisation of diagnosing and reporting of specific complication must be performed.…”
Section: Discussionmentioning
confidence: 99%